Influência do sistema de polimento e tratamentos de superfície na estabilidade de cor e rugosidade da resina composta - Lima, Thamires Diogo (2020)
Objectives: To evaluate (1) the influence of differents polishing systems on the stability color and surface roughness of composite resin and (2) the ability of different surface treatments to reduce the color changes without affect the surface roughness after the staining. Methods and materials: A total of one hundred and sixty disc-shaped specimens (8 x 2 mm) were prepared using a composite resin. The specimens were divided according to polishing systems: Negative control (NC), 3M system (3S), DhPro system (DS) and FGM system (FS). After this, the specimens were immersed in coffee for 48 hours. A new subdivision was performed according to surface treatment (n=10): ozonated gel (OG), hydrogen peroxide (HP), bicarbonate jet (BJ) and repolishing (R). Color change (ΔE00), whitening index (WI), opacity and surface roughness (Ra) were assessed at after polishing, after staining in coffee and after surface treatment. Data from ΔE00, WI and opacity did not present normal distribution and were submitted to Kruskal-Wallis. Multiple comparisons were performed by Tukey`s test. Two-way repeated measures ANOVA was used to analyze data from surface roughness at different assessment times. All pairwise multiple comparison procedures were conducted using the Tukey test. (α=0.05 significance level). Results: The higher staining presented on NC and DS. 3S and FS obtained similar results for color change, which means greater color stability. Surface treatments significantly reduced color changes and affected the surface roughness (p<0.001). Repolishing generated the greatest color change (p<0.001) in NC and DS groups. Conclusion: It was possible to conclude that the 3M polishing system obtained a higher color stability and lower surface roughness. Repolishing generates the highest color change values and is a viable option to avoid replacement the restoration.